Pravni okvir, relevanten za integracijo imigrantov v Sloveniji - Bešter, Romana (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
LEGAL FRAMEWORK RELEVANT TO THE INTEGRATION OF IMMIGRANTS IN SLOVENIA. This article provides an overview of the current Slovenian law on the integration of immigrants. It focuses on the following areas: long-term residence, family reunification, access to labour market, political participation, access to education, access to health and social care, housing, nondiscrimination and the acquisition of citizenship. The article presents the most recent changes to legislation in these areas, and exposes some of the weaknesses that hamper the integration of immigrants in Slovenia. Special attention is paid to comparison of different categories of immigrants - EU citizens, third country nationals and foreigners of Slovenian descent
Keywords: Slovenia; Slovenija; imigranti; integracija; tujci; zakonodaja